Demilitarization of the Russian Front after World War I - Zherdeva, Yulia A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article examines the demilitarization of the Russian Front after World War I. Demilitarization is understood as complex processes associated with the physical transformation of the war landscape and overcoming the toxic legacy of war: freeing the space from the presence of regular armies, military property, and military installations, as well as from the impact of specific war practices such as soil intoxication, water pollution, waterlogging of forests and fields, and deforestation. The aim of this study is to examine the institutions and mechanisms of demilitarization and demobilization of the Russian army in 1917–1918. The theoretical framework of this study draws on environmental history and postcolonial studies that allow the author to consider demilitarization through the prism of interaction with the environment and to understand its features in the former imperial boundaries. The paper works with materials of the Russian military archives, which help reconstruct the mechanisms of demobilization and the practices of demilitarization of the Russian Front. The author concludes that demobilization institutions were created in three stages, from May 1917 to May 1918: the first ones were established by the Stavka in May and supplemented in November 1917, but relatively “functional” demobilization institutions emerged in December and were associated with the Bolshevik administrative transformations. Whereas during the war demilitarization (clearing trenches and their surroundings of the effects of suffocating gases, sanitation, soil reclamation, and collecting weapons from battlefields) was practiced to preserve the army’s fighting ability, chaotic demobilization obscured these environmental issues with trivial problems of transportation and preservation of military property. The continental nature of the demilitarization of the former Russian Front makes it possible to speak of its remilitarisation as early as the summer of 1918.